To grade or not to grade: balancing formative and summative assessment in post-16 teacher trainee observations - Matthews, Richard; Noyes, Andrew (Taylor & Francis, 2016)
The issue of whether trainee teachers in the post-16 sector should have their classroom practice graded has been debated for a number of years. The case for training courses retaining an emphasis on written and verbal ‘developmental’ feedback at the expense of ‘judgements’ appears to be lost. This article is set within the context of an ever-growing culture of performativity in English further education colleges, where grading is regarded as an essential requirement to ensure high quality teaching. Tensions are explored between stakeholders who call for graded observations of trainees’ classroom performance (e.g. Ofsted and FEC quality assurance managers), and classroom-based trainers and researchers who argue that grading is too judgemental and compromises the formative and developmental progress of trainees. The rationale for trainee teachers to have their classroom practice graded is contrasted with evidence that highlights the negative results of grading. This article reports findings from the evaluation of an innovative, alternative strategy that addresses Ofsted’s central requirement for trainees to know ‘where they are’ in their development by offering a middle way between grading and not grading trainees’ classroom performance.